PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA KARTU GAMBAR ILUSTRASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS IV SEKOLAH DASAR - Virginia Annisa; Nur Fajrie; Muhammad Noor Ahsin (PGSD Universitas Muria Kudus, 2021)
The purpose of this study was to improve students' conceptual understanding and teacher skills by applying the Problem Based Learning learning model assisted by illustration image card media in grade IV SD N 4 Kalipucang Wetan.The research method used is Classroom Action Research (PTK) with reference to the Kemmis and Mc. Taggart which consists of four steps, namely 1) Planning, 2) Observation, 3) Implementation, and 4) Reflection. The subjects of this study were the fourth grade students of SD N 4 Kalipucang Wetan, totaling 21 students consisting of 7 female students and 14 male students. Data collection techniques using test and non-test techniques. The test technique is carried out through a learning evaluation test which is carried out at the end of the cycle, while the non-test techniques used include: 1) observation or observation including the teacher's skill observation sheet and the observation sheet for understanding the concept of attitude and skill aspects, 2) interviews, namely structured interviews, 3) documentation. The data checking technique used is the content validity of Expert Judgment. The data analysis technique was carried out in a descriptive comparative manner.The results showed that the use of the Problem Based Learning learning model could improve students' conceptual understanding of the knowledge aspect in the first cycle with an average score of 72.428. In the second cycle, the average score increased again by 75.285. Teacher skills in cycle I with an average score of 67% and cycle II an average score of 78%. Based on the data above, it can be concluded that using the Problem Based Learning model assisted by illustration image card media can improve students' conceptual understanding skills and teacher skills on the theme of the Beauty of Diversity in My Country in grade IV SD N 4 Kalipucang Wetan.